Assessing the Extent of Adherence to the Recommended Antenatal Care Content in Malaysia: Room for Improvement - Yeoh, P.L.; Hornetz, K.; Shauki, N.I.A.; Dahlui, M. (Public Library of Science, 2015)
Background Recent papers on monitoring of health services affirmed that while antenatal care (ANC) is an effective measure, quality is still a problem. Quality in maternal services "⋯involves providing a minimum level of care to all pregnant women⋯" Yet adherence to a minimum level of recommended ANC content appears to be unmet. Comprehensive review of ANC content rendered in environments with rapid changes in demographic, socio-economic, lifestyle and morbidity was sparse. Malaysia is such a country that has undergone these transitions with tremendous progress in health. However, recent progress in pregnancy outcomes is stagnating. This study aims to analyse adherence to recommended ANC; specifically, to examine the extent of adherence to recommended ANC content and to determine the factors influencing ANC content score. Methods A retrospective cohort study of 522 randomly selected women who used ANC was conducted. Data were extracted from individual records. The study examined adherence to essential ANC guidelines using weighted scoring for physical examination, health screening, case management, and health education. GLM Univariate analysis procedure was used to determine the factors associated with ANC content score. Binary logistic regression was used to assess ANC content level and pregnancy outcomes, controlled for ANC utilisation. Results Around half of the women had <80% of recommended ANC content documented. Health education had the lowest mean score, at around 35%. The low-risk pregnancies had a higher ANC content score than the high-risk pregnancies (78% vs. 75%; P = 0.002). The smallest clinics had a higher ANC content score than the bigger clinics (78% vs. 74-76%; P<0.001). ANC content score among the women with "adequate" ANC utilisation, as defined by the modified Adequacy of Prenatal Care Utilisation Index, was lower than the women with "adequate-plus" ANC utilisation (75% vs. 78%, P<0.001). Assessment of symphysis-fundal height, foetal presentation and foetal heart auscultation were initiated earlier than recommended. Inadequate ANC content was associated with higher prevalence of preterm birth. Conclusions Our findings indicate the presence of issues related to delivery of recommended ANC content. We advocate for all pregnant women to be ensured of adherence to the recommended ANC content. We also recommend monitoring the delivery of health advice. Conforming to recommended timing of initiation for ANC practices is essential due to resource implication and possible implication on maternal wellbeing. The association of inadequate ANC content and preterm birth may be due to lesser opportunities to receive some of the care because of lower number of ANC visits among preterm birth; this may also indicate the importance of having adequate ANC content.